Evaluation of changes in space control due to passing behavior in elite soccer using voronoi-cells - Rein, R.; Raabe, D.; Perl, J.; Memmert, D. (Proceedings of the 10th International Symposium on Computer Science in Sports (ISCSS), 2016)
A soccer player`s ability to make an "effective" pass in a play situation is considered one of the key skills characterizing successful performance in elite soccer (Bush, Barnes, Archer, Hogg, & Bradley, 2015; Hughes & Franks, 2005; Mackenzie & Cushion, 2013). However, although there is ample evidence in the literature that passing behavior is important it is much less clear what actually characterizes a "good" pass. One common topic investigated with respect to passing behavior in elite soccer is the frequency of passing events and their correlation with game performance (Lago-Penas, Lago-Ballesteros, Dellal, & Gomez, 2010; Liu, Gomez, Lago-Penas, & Sampaio, 2015). Results from this line of research show for example that the number of passes made during the FIFA World cup finals between 1966 and 2010 continuously increased (Wallace & Norton, 2014) and that the number of crosses and assists are positively related to game performance (Lago-Penas et al., 2010; Luhtanen, Belinskij, Häyrinen, & Vänttinen, 2001). Similar, Hughes and Franks (2005) found that longer passing sequences increase the goal scoring likelihood (see also Yiannakos & Armatas, 2006). Although all these studies provide valuable information regarding the importance of passing behavior in elite soccer it remains unclear what characterizes successful passing. Accordingly, it is not known which effects individual passes exert on concrete game play situations which impedes the application of research findings by practitioners. Here, we introduce a novel approach to evaluate individual passing behavior during game play using Voronoi cells to investigate changes in space control.